Analisis Kebutuhan Kapasitor Bank Pada MCC 200 Untuk Meningkatkan Faktor Daya Di PT. Ecogreen Oleochemicals Batam - Niko Franceda Silalahi; Muhammad Erpandi Dalimunthe; Haris Gunawan (CV. Hawari, 2026)
Power factor is a critical parameter in industrial power systems, affecting the efficiency of electrical energy use. A low power factor due to the dominance of inductive loads can lead to increased current, power losses, reduced voltage quality, and wasted distribution equipment capacity. This study aims to analyze the need for a capacitor bank in the Motor Control Center (MCC) 200 at PT. Ecogreen Oleochemicals Batam to improve the system's power factor. The research method involved measuring electrical parameters, analyzing reactive power, and calculating the capacitor bank requirement based on actual load conditions. The results showed that an initial power factor of 0.78 could be increased to 0.95 with the installation of a 150 kVAR capacitor bank. The implementation of the capacitor bank reduced the system current by 17.96% and reduced reactive power by 58.98%. The results demonstrate that the installation of a capacitor bank is effective in improving the efficiency of the power distribution system and supporting energy conservation in industrial environments.